Long‐Wavelength Gravity Field Constraint on the Lower Mantle Viscosity in North America. Issue 12 (25th November 2020) - Reusen, J. M.; Root, B. C.; Szwillus, W.; Fullea, J.; van der Wal, W.
Abstract: The long‐wavelength negative gravity anomaly over Hudson Bay coincides with the area depressed by the Laurentide Ice Sheet during the Last Glacial Maximum, suggesting that it is, at least partly, caused by glacial isostatic adjustment (GIA). Additional contributions to the static gravity field stem from surface dynamic topography, core‐mantle boundary (CMB) topography, and density anomalies in the subsurface. Previous estimates of the contribution of GIA to the gravity anomaly range from 25% to more than 80%. However, these estimates did not include uncertainties in all components that contribute to the gravity field. In this study, we develop a forward model for the gravity anomaly based on density models and dynamic models, investigating uncertainty in all components. We derive lithospheric densities from equilibrium constraints but extend the concept of lithospheric isostasy to a force balance that includes the dynamic models. The largest uncertainty in the predicted gravity anomaly is due to the lower mantle viscosity, uncertainties in the ice history, the crustal model, the lithosphere‐asthenosphere boundary, and the conversion from seismic velocities to density have a smaller effect. A preference for lower mantle viscosities >10 22  Pa s is found, in which case at least 60% of the observed long‐wavelength gravity anomaly can be attributed to GIA. This lower bound on the lower mantle viscosity has implications for inferences based on models for mantle convection and GIA. Plain Language Summary: About 26, 000 years ago, vast parts of North America and Northern Europe were covered by ice sheets. These glaciations depressed the ground, which is rebounding ever since the ice sheets started melting. The rate of this rebound depends on the structure of the earth below it. In this paper, we obtain more insight into the structure of the earth. To do so, we use the gravitational field since we can observe small deviations in this field very precisely. Over Hudson Bay, we observe such a deviation. The observed gravity anomaly over Hudson Bay closely resembles the area previously covered by ice. One possible explanation for this anomaly is therefore the incomplete rebound of the land. To test this, we include the effects of previous glaciations and mantle flow in a model of the crust and the lithosphere. We vary the viscosities of the upper and lower mantle, which are important parameters when modeling glacial rebound and mantle flow. The best match is found for a stiff lower mantle, implying that at least 200 m of land uplift remains and that a minimum of 60% of this anomaly can be attributed to the depression caused by past glaciations. Key Points: We model the gravity anomaly in Laurentia resulting from crustal and lithospheric inhomogeneities, GIA, and mantle convection We extend the concept of lithospheric isostasy by including the forces from GIA and surface dynamic topography (DT) Best fitting models have a lower mantle viscosity larger than 10 22  Pa s